Congress of Neurological Surgeons Systematic Review and Evidence‐Based Guidelines on Pathological Methods and Prognostic Factors in Vestibular Schwannomas. Issue 2 (February 2018) - Sughrue, Michael E; Fung, Kar‐Ming; Van Gompel, Jamie J; Peterson, Jo Elle G; Olson, Jeffrey J
Abstract : TARGET POPULATION : Adults diagnosed with vestibular schwannomas. QUESTION 1 : What is the prognostic significance of Antoni A vs B histologic patterns in vestibular schwannomas? RECOMMENDATION : No recommendations can be made due to a lack of adequate data. QUESTION 2 : What is the prognostic significance of mitotic figures seen in vestibular schwannoma specimens? RECOMMENDATION : No recommendations can be made due to a lack of adequate data. QUESTION 3 : Are there other light microscopic features that predict clinical behavior of vestibular schwannomas? RECOMMENDATION : No recommendations can be made due to a lack of adequate data. QUESTION 4 : Does the KI‐67 labeling index predict clinical behavior of vestibular schwannomas? RECOMMENDATION : No recommendations can be made due to a lack of adequate data. QUESTION 5 : Does the proliferating cell nuclear antigen labeling index predict clinical behavior of vestibular schwannomas? RECOMMENDATION : No recommendations can be made due to a lack of adequate data. QUESTION 6 : Does degree of vascular endothelial growth factor expression predict clinical behavior of vestibular schwannomas? RECOMMENDATION : No recommendations can be made due to a lack of adequate data. The full guideline can be found at:https://www.cns.org/guidelines/guidelines‐management‐patients‐vestibular‐schwannoma/chapter_6 .